Constitutionality and Legality Of the Curfew as a Measure To Contain Infectious Diseases: The Case of COVID-19 - Oštir, Sergeja (Medicine, Law & Society, 2026)
The state must protect public health and prevent the spread of infectious diseases, often by limiting certain human rights. While quick action is crucial, it must align with constitutional safeguards. During the COVID-19 epidemic, Slovenia introduced a curfew that lasted 174 consecutive days. However, the Constitutional Court of the Republic of Slovenia did not assess its constitutionality, as it dismissed the related initiatives. This article examines the curfew’s legal basis, the constitutional standards governing such measure, and whether the ordinances met the requirements of legality, necessity, and proportionality in a democratic society. The findings show that the curfew in Slovenia was introduced on an unconstitutional legal basis, and the constitutional-law analysis conducted in this article further confirms its incompatibility with the Constitution of the Republic of Slovenia.